Performance Evaluation of Optical Modulators in Optical Fiber Communication Systems - Abusale, Wahhab Abdulrzzaq; Karabulut, Muhammet Ali; Ilhan, Haci (IEEE, 2022)
In this paper, we evaluate the performance of optical modulators may be categorized into amplitude (AM), phase (PM), frequency (FM) and Mach Zehnder ( ZM) by observing the effect of three parameters (Q.MaxFactor, BER, Eye Height) with different lengths of optical fiber (25km, 50km). Firstly, the performance of each modulation type separately with varying sizes of optical fiber is analyzed for three different bit rate values (1, 5, 10 Gb/s) and the number of samples per bit ( 16, 32, 64). Then using the wavelength division multiplexing (WDM) technic, we analyze four types of optical modulators (AM, PM, FM and ZM) in single mode fiber. It can be deduced from the obtained results that the AM and MZ modulators are more efficient in fiber because it has maximum Q.Max factor and minimum BER values than the other types.
Keywords: BER; Eye Height; Optical Fiber Communication; Optical Modulators; Q-Factor; Computer Science; Engineering; Telecommunications